Interdisciplinary surgical and orthodontic treatment of odontogenic keratocyst of the mandibular body in a 12-year-old female patient, with a relapse after 7 years of observation: a case report - Rączkiewicz, Maciej; Parchańska-Kowalik, Monika; Stós, Wojciech; Stypułkowska, Jadwiga; Loster, Bartłomiej W. (Journal of Stomatology, 2018)
Odontogenic keratocyst, until recently known as keratocystic odontogenic tumor, is a developmental, odontogenic cyst originating from a dental follicle. It is characterized by aggressive and quite fast growth, with a high tendency of recurrence (about 62% of cases). The following article presents a full description of interdisciplinary surgical-orthodontic treatment of a patient who, at the age of 12, was diagnosed with a large keratocyst of the medial region of the mandible, including unerupted teeth: 43, 44, and 45. In addition, partial retention of teeth 23 and 35 was found. Surgical treatment was performed using a two-stage method, with a 7-year follow-up period, during which impacted tooth 43 was removed, and teeth 24 and 36 were also removed. During orthodontic treatment, the acrylic plug was placed in the fenestration area, further orthodontically assisted eruption of dislocated by the cyst teeth 44 and 45, with the use of a removable orthodontic appliance and subsequently, the alignment of the upper and lower teeth with fixed appliances. After completion of orthodontic treatment, 7 years after the cyst enucleation, radiological examination was performed, which revealed a circular lesion in the projection of the roots of the lower teeth with a diameter of about 8 mm, suggesting the presence of cyst relapse. The lesion was enucleated, and the result of the histopathological examination confirmed the diagnosis.